KUALITAS FISIKA DAN KIMIA KOMPOS ECENG GONDOK (Euchornia crasipess) MENGGUNAKAN AKTIVATOR EM-4 - Hikma Yani; Rahmawati Rahmawati; Faidha Rahmi (Universitas Muhammadiyah Jakarta, 2018)
ABSTRACT: This study aims to determine the quality of water hyacinth compost in physical and chemical properties. Water hyacinth is considered a weed that damages the aesthetics and aquatic environment in the Lut Tawar Lake tourist area. A solution is needed to overcome these problems, one of which is composting. In order for composting to take place faster, an EM-4 activator will be used which will give good quality. This research method uses one replicate with three treatments (K1 and K2 using EM-4, and K0 without EM-4). This study was conducted in two stages, that are the composting and characterization stages. The composting process is let runs for 60 days. Checking every 5 days is turn upside down and physical observation. After the composting process, is determined the pH, temperature and characterization. Characterization is done to determine the levels of C, N, P, K, Ca and Mg. The results of this study showed that EM-4 is effective for carbon (C), phosphorus (P) and calcium (Ca) grade. The grade of macro nutrient (C, N, P, K), micro nutrient (Ca) and temperature of water hyacinth compost are suitable with SNI.